Flagship of Scholarship on Indonesian Islam: In Memoriam Azyumardi Azra (1955-2022) - Oman Fathurahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
Almost everybody who knew him is convinced that Azyumardi Azra, CBE has left us much too early. This Professor in History at the Faculty of Adab and Humaniora at the State Islamic University Syarif Hidayatullah in Jakarta passed away on 18 September 2022 in a hospital in Serdang, Selangor, Malaysia. Inna lillāhi wa inna ilaihi rāji‘un.Two days earlier, Professor Azra suffered from health issues while traveling by airplane to Kuala Lumpur, Malaysia. He was not on his way for holiday purposes after travel restrictions had finally been lifted after the pandemic. Rather, he was invited by the Angkatan Belia Islam Malaysia (ABIM) to speak at an international seminar about “Cosmopolitan Islam, Inspiring Awareness, Exploring the Future” at the Bangi Avenue Convention Centre (BACC), in Kajang, Malaysia.Azra was widely known as an extremely prolific Indonesian Muslim intellectual who was active in many scholarly forums in Indonesia and in the world at large. Some of his colleagues indeed saw him as a wandering intellectual much like Ibnu Batutah. He devoted most of his time and dedication to the study of Indonesian and Southeast Asian Islam and he was one of the most brilliant Islamic intellectuals of the century in this field.